ANALYSIS OF DEMAND FOR BEEF DISTRICT OF JEMBER - Nuriza Utami; henik prayuginingsih; Annisa Nurina Aulia (Universitas Muhammadiyah Jember, 2019)
Beff is a kind of foodstuff which relatively expensive, so not every household can buy it every time. This study aimed to: (1) analyze the factors that influence demand of beef at District of Jember, and (2) calculate the elasticity on price and income of demand of beef , also cross-elasticity of demand due on prices of other goods. This study used descriptive methods and surveys with deliberate regional selection (purposive method), selected sub district were Sumbersari, Patrang, Kaliwates, Jelbuk, Mayang, Tempurejo, Ambulu, and Sumberbaru. Sampling was carried out in proportioned random sampling with total of 72 respondents, data obtained from interviews community. Data analysis method used demand theory and Cobb-Douglas model multiple regression analysis. The results of this study concluded that: (1) the factors that significantly influence demand of beef at District of Jember were price of beef and fish , household income, dummy tasts and dummy research area, while the price factor of chicken meat, prices of eggs, education level , while number of family members hae no significant effect on.; (2) beef price elasticity was -4,701 showed that elsticity of beef was elastic, cross elasticity of chicken meat price, price of eggs and fish were 3,907; 4,416; 1,311, which showed that the three items were substitutes of beef, the income elasticity of 0,579 indicates that beef was a normal item, that was consumtion goods, which was in the event of an increasing on income will caused increase demand.